Effect on Ubiquinone MDA Level of Plasma, FEV1% and CAT Score Stable COPD Patients - Ardorisye Fornia; Suradi Suradi; Aphridasari Aphridasari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Background: Oxidation stress showed clinical evidence of increased in patients with COPD and contribute functionally to expiratory air flow resistance, so the body requires exogenous antioxidants to inhibit oxidative stress. This study was conducted to assess whether there is influence on levels of MDA plasma ubiquinone, FEV1% and patients with stable COPD CAT score. Methods: This study is a clinical trial experimental with pretest and post-test design which aims to determine the effect of plasma MDA, FEV1% and patients with stable COPD CAT score. Subjects consist of 30 patients with stable COPD who came to Pulmonary outpatient clinic of Moewardi hospital Surakarta during June to August 2016. The sample was taken by consecutive sampling. Subjects were divided into two group, the treatment group (n=15) received additional therapy ubiquinone 1x150mg/day and the control group (n=15) received standard therapy. MDA plasma levels, FEV1% and CAT scores were measured at the time of control pulmonary outpatient clinic. Results: Giving ubiquinone can significantly lower CAT score better in the treatment group compared to the control group. There were no statistically significant difference (p=0.744) in plasma MDA treatment group (1.37 ± 0.11) compared to controls (1,39 ± 0.16). There were no statistically significant difference between (p=0.276) the decline in FEV1% treatment group (43.28 ± 20.59) and the control group (36.01 ± 14.73). Conclusion : The use of Ubiquinone in decreasing CAT score for stable COPD patients. There was lowering effect in MDA plasma but there was no excalation value in FEV1%.